2008
DOI: 10.1111/j.1365-2834.2008.00939.x
|View full text |Cite
|
Sign up to set email alerts
|

Revitalizing the charge nurse role through a bespoke development programme

Abstract: Aims  This article describes the genesis, contents and outcomes of a bespoke Charge Nurse Development Programme which was designed to enhance the propensity of nurses to manage in an acute hospital setting. Background  The charge nurse role is pivotal to the provision of high‐quality care and effective ward management. However, many nurses are promoted to these roles of substantial responsibility commonly with no formal management preparation, an inherent under‐confidence and in some cases a tangible reluctanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 5 publications
1
17
0
Order By: Relevance
“…In particular, SCNs expressed that a structured in‐house programme for role induction, in addition to ongoing coaching and/or mentoring, would greatly benefit their leadership abilities. This finding is supported by previous research which identified the critical role of education, training and structural support for the development of leadership and managerial skills (Platt & Foster , McCallin & Frankson , Sherman et al . ).…”
Section: Discussionsupporting
confidence: 84%
“…In particular, SCNs expressed that a structured in‐house programme for role induction, in addition to ongoing coaching and/or mentoring, would greatly benefit their leadership abilities. This finding is supported by previous research which identified the critical role of education, training and structural support for the development of leadership and managerial skills (Platt & Foster , McCallin & Frankson , Sherman et al . ).…”
Section: Discussionsupporting
confidence: 84%
“…The growing realization that participants were not alone in their difficulties encouraged others to share their experiences and this promoted feelings of mutual support, understanding and collegiality. Platt and Foster (2008) identified similar issues in their work with charge nurses across one NHS Hospital Trust, reporting that many participants led insular working lives with little, if any, working relationship with peers in other areas, thus missing opportunities for support.…”
Section: Discussionmentioning
confidence: 99%
“…A questionnaire was designed, drawing upon the published literature (Fairbairn Platt and Foster, 2008;Hay Group, 2006;Pegram et al, 2014;RCN, 2009) and the data derived from focus groups which were held with some ward managers. In addition to specially developed items addressing the topics of interest (aspects of the role, challenges and enablers), four frequently used and validated instruments with good psychometric properties were included in the questionnaire to enable comparison with normative data regarding the sample's perceived job satisfaction, occupational stress, professional identification and commitment to the healthcare provider.…”
Section: Data Collection Instrumentmentioning
confidence: 99%